Razogljičenje in rekristalizacija neorientirane elektro pločevine - Steiner Petrovič, Darja (Kovine zlitine tehnologije, 1995)
The kinetics of decarburization process of industrially and laboratorially manufactured cold rolled non-oriented silicon steel sheets was investigated. Samples of the different electrical steel sheets were decarburized by annealingin wet hydrogen with different dew points and at different times and the carbon content was measured. The recrystallization of decarburized and undecarburized samples of electrical steels, which were annealed in a lead bath, was investigated. The microstructure was examined and average grain size was determined.
Keywords: Metallurgical and Materials Engineering; metalurgija; elektropločevina; rekristalizacija; razogljičenje